A learned and fruitefull commentarie vpon the Epistle of Iames the Apostle, vvherein are diligently and profitably entreated all such matters and chiefe common places of religion as are touched in the same epistle: / written in Latine by the learned clerke Nicholas Hemminge, professour of diuinitie in the Vniuersitie of Hafnie, and nevvly translated into English by VV.G. [electronic resource] :
Summary goes here